Using the comet and micronucleus assays for genotoxicity studies: a review - Araldi, Rodrigo Pinheiro [UNESP]; Melo, Thatiana Corrêa de; Mendes, Thais Biude [UNESP]; De Sá Júnior, Paulo; Nozima, Bruno Heidi Nakano; Ito, Eliana Tiemi [UNESP]; Carvalho, Rodrigo Franco de; Souza, Edislane Barreiros de [UNESP]; Stocco, Rita de Cassia (Elsevier, 2015)
Physical, chemical and biological agents can act in the DNA, resulting in mutation involved in cancer. Thus, genotoxic tests are required by regulatory agencies in order to evaluate potential risk of cancer. Among these tests, the comet assay (CA) and micronucleus assay (MNA) are the most commonly used. However, there are different protocols and recommendations already published. This is the first review, after the inclusion of CA in S2R1 guidance and OECD 489, which summarizes the main technical recommendations of both CA and MNA.
Keywords: Genotoxicity tests; Comet assay; Micronucleus assay; Mutagenesis